Resveratrol and anti-atherogenic effects. (18th August 2015) - Riccioni, Graziano; Gammone, Maria Alessandra; Tettamanti, Guido; Bergante, Sonia; Pluchinotta, Francesca Romana; D'Orazio, Nicolantonio
Abstract: The role of inflammation and oxidative stress in atherosclerosis development has been increasingly well recognized over the past decade. Inflammation has a significant role at all stages of atherosclerosis, including initiation, progression and plaque formation. Resveratrol is a naturally occurring polyphenolic compound found in grape products, berry fruits and red wine. Its ability to behave therapeutically as a component of red wine has attracted wide attention. Accumulating evidence suggests that it is a highly pleiotropic molecule that modulates numerous targets and molecular functions. Epidemiological studies indicate that the Mediterranean diet, rich in resveratrol, is associated with a reduced risk of atherosclerosis. Resveratrol is believed to decrease circulating low-density lipoprotein cholesterol levels, reduce cardiovascular disease risk; it reduces lipid peroxidation, platelet aggregation and oxidative stress. Resveratrol is considered a safe compound, since no significant toxic effects have been demonstrated after administration of a broad range of concentrations, and an effective anti-atherogenic agent.